"Impact of drug‐reimbursement policies on prescribing: A case‐study of a newly marketed long‐acting injectable antipsychotic among relapsed schizophrenia patients". Issue 1 (23rd November 2017) - Jackson, John W.; Fulchino, Lisa; Rogers, James; Mogun, Helen; Polinski, Jennifer; Henderson, David C.; Schneeweiss, Sebastian; Fischer, Michael A.
Abstract: Objective: To quantify and explain variation in use of long‐acting injectable antipsychotics (LAIs) in the United States, and understand the relationship between patient characteristics, drug reimbursement policies, and LAI prescribing after relapse. Methods: A cohort of recently relapsed patients with schizophrenia ages 18 to 64, were identified immediately after discharge from a related inpatient hospitalization, partial hospitalization, or emergency room visit, drawn from 2004 to 2006 Medicaid claims, and followed for 90 days until LAI initiation. Data on state‐level Medicaid prior authorization (PA) policies for LAIs were collected. Sequential longitudinal Poisson regression models were developed to understand the relationship between patient and PA policy variables and LAI prescribing, including prior adherence to oral antipsychotics, demographics, clinical variables, and presence of PA policy for LAI. Results: Among 36 282 patients, 3.1% received risperidone LAI, and 3.8% received a first‐generation (FGA) LAI with wide variation across states. Prior adherence ranged from 29% to 89% but was marginally associated with initiation and did not explain variation for LAI prescribing. FGA initiation was associated with geography and race/ethnicity but not PA policy. For risperidone LAI initiation, demographics and clinical factors explained, respectively, 5.0% and 3.0% of the variation; PA policy had a large negative association with initiation (RR = 0.41; 95%CI 0.20–0.87) and explained 8.4% of the variation. Conclusions: PA policies may represent a major treatment barrier for risperidone LAI among relapsed patients. Non‐adherence plays a little role in predicting which patients receive LAIs. Policy makers and health insurers will need to consider these findings when guiding the use of LAIs. KEY POINTS Among a nationwide cohort of relapsed schizophrenia patients enrolled in US Medicaid, 3.1% received Risperdal Consta, a long‐acting injectable antipsychotic (LAI), and 3.8% initiated a first‐generation first‐generation LAI within 90 days after discharge. During 2004 to 2006, there was marked variation in 90 day post‐relapse initiation of Risperdal‐Consta—a newly marketed medication during this period—and also marked variation in 90 day post‐relapse initiation of any first‐generation LAI, which appeared to be associated with race/ethnicity and geography. Prior authorization policies were associated with substantially lower initiation of Risperdal Consta in this cohort of relapsed patients even after accounting for clinical indication (non‐adherence), relapse history, demographics, adjunctive medication, and mental health service use.